2020
DOI: 10.1007/s00784-020-03385-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipoxin A4 on E. coli LPS-induced osteoclastogenesis

Abstract: Objectives The objective of the present study was to investigate the effect of lipoxin-type A4 (LXA4) on bacterial-induced osteoclastogenesis. Material and methods Human periodontal ligament cells (PDLCs) in coculture with osteoclast precursors (RAW264.7 cells) were exposed to bacterial stimulation with lipopolysaccharide (LPS) to induce inflammation. After 24 h, cells were treated to 100 ng/ml of LXA4 and 50 ng/ml of forymul peptide receptor 2 (FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…With respect to bone metabolism, several studies demonstrated the ability of SPMs to prevent bone resorption by inhibiting gene expression. SPMs have been shown to inhibit mRNA expression of osteoclastogenesis promoting transcription factors (i.e., NF‐κB, NFATcl and c‐fos), which normally function to promote osteoclastic differentiation by activating the expression of osteoclast‐specific genes (e.g., TRAP, cathepsin K, and MMP‐9) [16, 121–123]. For instance, RvE1 has been shown to inhibit the expression of osteoclast‐specific genes by decreasing nuclear translocation of transcription factors from the cytoplasm to the nucleus in osteoclast precursor cells in vitro [124].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to bone metabolism, several studies demonstrated the ability of SPMs to prevent bone resorption by inhibiting gene expression. SPMs have been shown to inhibit mRNA expression of osteoclastogenesis promoting transcription factors (i.e., NF‐κB, NFATcl and c‐fos), which normally function to promote osteoclastic differentiation by activating the expression of osteoclast‐specific genes (e.g., TRAP, cathepsin K, and MMP‐9) [16, 121–123]. For instance, RvE1 has been shown to inhibit the expression of osteoclast‐specific genes by decreasing nuclear translocation of transcription factors from the cytoplasm to the nucleus in osteoclast precursor cells in vitro [124].…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [18] observed that LXA4 inhibited polymethylmethacrylate (PMMA)‐upregulated production of TNFα, IL‐1β, PGE2, and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) in a dose‐dependent manner. Furthermore, LXA4 counteracted RANKL/LPS‐induced formation and function of osteoclasts in an in vitro co‐culture model composed of primary human PDLFs and murine RAW246.7 cell line [123]. LXA4 suppressed RANKL/LPS‐induced upregulation of osteoclast‐associated genes (e.g., RANKL, TRAP, cathepsin K), TRAP activity, and the number of TRAP‐positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the percentages of biofilm production identified in the strains were comparable to those previously reported in highly pathogenic UPEC strains [ 44 ]. Additionally, it has been suggested that E. coli lipopolysaccharides (LPS) may have a role in the inflammatory processes associated with periodontal disease [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] In co-cultures of periodontal ligament cells and osteoclast precursor cells, the addition of LPS increased the number of osteoclasts. 56,57 E. coli LPS stimulates the production of RANKL and prostaglandin E2 (PGE2) through TLR4 in osteoblasts, which promotes the formation of osteoclasts in co-cultures of osteoblasts and bone marrow cells (including osteoclast progenitor cells). 58,59 Similarly, E. coli LPS and Actinomycete LPS increased the expression of RANKL in periodontal ligament cells.…”
Section: The Effect Of Oral Microbiome On Periodontal Inflammation An...mentioning
confidence: 99%